ELECTORAL VIOLENCE AND POLITICAL APATHY IN NIGERIA FOURTH REPUBLIC - Stephenson Grace Ladi; Samuel Agwojogwa Stephenson (International Studies Journal)
This paper examines the nexus between electoral violence and political apathy in Nigeria. Electoral violence is one of the factors that precipitate the contemporary political apathy that threaten democratic consolidation because; democracy cannot thrive without popular majority participation in electioneering process. It looks at some conceptual clarification after reviewing some literature on electoral violence.  After a critical look at some of the various causes of electoral violence in the country, the writer discovers that a high level of uncontrollable electoral violence will lead to unmitigated level of political apathy. It is against this background that it recommends amid others: the strengthening of Electoral Act, 2022 as amended; political campaign should be based on issues and not on individual personality, condemnation of money politics, intra-party democracy and the creation of a level play-ground for all political contestants etc; that will prevent electoral violence and a panacea to mitigate the level of political apathy.